POLA KERJA JURNALIS INFOTAINMENT (STUDI KUALITATIF PADA PT. BINTANG ADVIS MULTIMEDIA, CREATIVE INDIGO PRODUCTION, DAN PT. SHANDIKA WIDYA CINEMA – JAKARTA) - Sri Pangestuti; Atika Tyas Utami (Jurnal Ilmu Komunikasi, 2008)
The growth of journalism, now days, has been following market demand. The global condition, such as capitalism and social politic situation have contributed significant impact to television programs. This research is entitled “The Pattern of Work Infotainment Journalist (Descriptive Study at PT. Bintang Advis Multy Media, Creative Indigo Production, and PT. Shandihika Widya Cin- ema) at Jakarta-Indonesia. It aims at revealling the thruth of assumsion among television audi- ence, as well as, to understand the work modelis accured in the infotainment program. Result of the research are : there is deviation of paradigm on the infotainment program, such as, a program which is inserted with amusement has become a program “gossip” / intriguye in fact, it said by the “ Persatuan Wartawan Indonesia” that program is part of journalism. The pattern of work at infotainment of work is linier think.